An anonymous foe. (Economist, 2011)
The article discusses incidents of computer hacking. Victims have included the International Monetary Fund and consumer-electronics maker Sony. Most attacks are conducted by private groups such as Anonymous and Lulz Security, rather than by government organizations. Organized-crime groups are also involved in hacking, and their methods are becoming increasingly sophisticated.